EXPLORING THE IMPACT OF DIGITAL SCREEN USE ON EYE HEALTH AND MYOPIA (Journal of Medical & Health Sciences Review, 2025)
Background: With the increasing prevalence of digital screens in daily life, concerns regarding their impact on eye health, especially myopia, have emerged. Myopia, or nearsightedness, has been linked to prolonged screen use, but the strength and nature of this relationship remain unclear. This study explores the impact of digital screen use on eye health, particularly myopia, and related symptoms such as digital eye strain.Objective: To examine the relationship between digital screen exposure and the development or progression of myopia, as well as other eye health issues like eye strain, dry eyes, and blurred vision.Methods: A cross-sectional survey was employed to collect quantitative data from a diverse sample of 250 participants. A structured questionnaire was used to gather information on-screen usage habits (e.g., daily screen time, device types), eye health (e.g., presence of myopia, eye strain symptoms), and protective measures (e.g., use of blue light filters, frequency of breaks). Data were analyzed using descriptive statistics, normality tests (Shapiro-Wilk), Cronbach's Alpha for reliability, and Pearson's correlation for validity.Results: The Shapiro-Wilk test revealed that the "Awareness of impact on eye health" and "Overall eye health" data were not normally distributed. Cronbach's Alpha for related scales was very low (0.008), indicating poor internal consistency. Correlation analysis showed weak associations between screen use, outdoor activity, and myopia, with only minimal relationships between these factors and the perceived changes in vision due to screen exposure.Conclusion: The study highlights that while digital screen use may play a role in eye health issues such as myopia, the relationships between these variables are weak and complex. The low reliability of the scales suggests that measurement tools need to be refined. Future research should explore other factors influencing eye health, such as genetic predisposition, and use more robust data collection methods to fully understand the long-term impact of screen exposure on vision.